PUBLIC MANAGEMENT OF INNOVATIONS IN THE SOCIO-HUMANITARIAN SPHERE: CHALLENGES AND WAYS TO OVERCOME - Moisiiakha, Andrii (Global Prosperity, 2021)
EU integration and globalization trends require new mechanisms and methods of regulating economic processes to transform Ukraine into an economically developed powerful state. Innovation is an integral part of any production cycle, but to achieve better results, innovation processes and relationships in the creation and implementation of innovative technologies in the national economy require active participation and great attention from the state. The main emphasis of such attention should be focused on organizational, legal and institutional support of innovation, which requires solving a vast number of problems of intensive development. The end of the twentieth century was a period of spreading ideas about the need to change the paradigm of public administration. Scientists began to realize the need to move to a new model of public administration based on strengthening the social nature of government. The change in approach implies an essential change in the state’s role: from the producer of public goods to the regulator of market processes. During the implementation of this model, the most crucial effect is possible if the principles of openness, innovation, decentralization, and a combination of market and state regulation, individual freedom and new forms of individual and collective responsibility.